Nucleoside-modified AdoMet analogues for differential methyltransferase targeting. Issue 14 (23rd January 2020) - Cornelissen, Nicolas V.; Michailidou, Freideriki; Muttach, Fabian; Rau, Kristina; Rentmeister, Andrea
Abstract : Methyltransferases modify a wide range of biomolecules using S -adenosyl-l -methionine (AdoMet) as cosubstrate. Enzymatic generation of nucleoside-modified AdoMet analogues and conversion by different methyltransferases is shown. Abstract : Methyltransferases (MTases) modify a wide range of biomolecules using S -adenosyl-l -methionine (AdoMet) as the cosubstrate. Synthetic AdoMet analogues are powerful tools to site-specifically introduce a variety of functional groups and exhibit potential to be converted only by distinct MTases. Extending the size of the substituent at the sulfur/selenium atom provides selectivity among MTases but is insufficient to discriminate between promiscuous MTases. We present a panel of AdoMet analogues differing in the nucleoside moiety (NM-AdoMets). These NM-AdoMets were efficiently produced by a previously uncharacterized methionine adenosyltransferase (MAT) from methionine and ATP analogues, such as ITP and N 6 -propargyl-ATP. The N 6 -modification changed the relative activity of three representative MTases up to 13-fold resulting in discrimination of substrates for the methyl transfer and could also be combined with transfer of allyl and propargyl groups.